Extremism, Counter-terrorism and Policing. - Blakemore, Brian (Taylor and Francis, 2016)
This book brings together a diverse range of multidisciplinary studies on policing violent extremism and terrorism, written by experts in the field. These studies provide a detailed understanding of government policy and methods on tackling extremism from a policing and community level and explore the historical development, the present situation and future trends in this area. The book offers an important contribution to academic and policy debate surrounding extremism, its causes, and treatments and is of interest to policing professionals, policy-makers and academics.